Searching for sustainability : interdisciplinary essays in the philosophy of conservation biology - Norton, Bryan G. (Cambridge studies in philosophy and biology., 2003)
This book examines from a multidisciplinary viewpoint the question of what we mean by setting sustainability as a goal for environmental management. The author explores ways to break down the disciplinary barriers to communication and deliberation about environment policy, and to integrate science and evaluations into a comprehensive environmental policy.